NATIONAL INNOVATIVE SYSTEM IN THE USA: INSTITUTIONAL ASPECTS - A. V. Frolov (Russian Journal of Economics and Law)
The article reveals the institutional aspect of the USAS national innovative system (NIS). It shows how the functioning of anti-monopoly and patent legislation can stimulate innovative development or bar it. The main initiatives of the USA government on improving the NIS legal base are viewed as an essential institutional factor.